PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP KEPUASAN PELANGGAN PADA HOTEL PELANGI MALANG - ROZZAQU NORMA; YUSUF RISANTO (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purposes of this research are to find out the influence of Customer Relationship Management (CRM) variable which consists of identification variable, customer differentiation variable, interaction variable to customers and simultaneously modification variable to the customers' satisfaction at Pelangi Hotel Malang. Respondents characteristics in this research are taken based on their gender, age, occupation, the information they have about Pelangi Hotel Malang, and how often they stay there as well. The measurements of CRM are using two variables, independen variable (X) and dependen variable (Y). The populations that had been researched in this research, are the entire Pelangi Hotel Malang's customers on 2015 and are already fulfilled the criteria that is required before. Data analysis is done by using descriptive analysis test and statistic inferential analysis, and also hypothetical test by using double linear regression test. The result of this research shows that Identified Variable (X1), Customer Differentiation Variable (X2), Interaction with Customer (X3), and Modification Variable (X4) simultaneously and partially, have significant influences to Customers' Satisfaction Variable (Y) at Pelangi Hotel Malang. Keywords: Customer Relationship Management, Customer Satisfaction, identification, differentiation, interaction with customer, modification.